Restoring the memories of places at the Nicolaus Copernicus University (NCU). On the process of students’ learning through popularization activities - Majchrzak-Ptak, Kinga (Adult Education Discourses, 2020)
This paper presents considerations regarding the results of idiographic research carried out within the course of four cycles of an interdisciplinary project: „Students towards the places of (non)memory at Nicolaus Copernicus University”. On a theoretical level, the project was based, among other things, on the concept of memorial sites of Pierre Nora. In terms of methodology the project was based on action research supported by the analysis and interpretation of empirical data collected through the search for sources, (focus) interviews and (self)observation which was subject to thick description. On a didactic level, the project was built around the assumptions of a critical and emancipation paradigm of student education. In the presentation of the results of the project, emphasis was placed on the description of the multi-faceted process of learning by organizing popularizing activities. The process gave project participants the opportunity to be the subjects of their own practice, and its multi-faceted cognition, which fostered critical reflection – by taking into account the context or feedback – and resulted in the formulation of conclusions for the future. In order to show the specificity of the presented process, the text shows the characteristics of the stages of implementation of individual popularization initiatives (planning and preparation stage, public presentation stage and evaluation stage).